Pengaruh Work-Life Balance terhadap Kinerja Karyawan melalui Kepuasan Kerja pada BPJS Ketenagakerjaan Kantor Cabang Surabaya Karimunjawa - Achmad Fathur Asari (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study aimed to determine and analyze the effect of work-life balance on employee performance through job satisfaction as a mediating variable at BPJSTK Surabaya Karimunjawa. This survey is a quantitative approach to 30 employees. The statistical analysis of this research is PLS (Partial Least Square) with PLS 3.0 software. The Likert scale is used as a measurement scale. The survey results show that work-life balance affects employee performance. In addition, work-life balance also has an impact on job satisfaction. Job satisfaction has a significant and positive effect on employees, which causes the company to improve the performance of its employees through aspects that make employees feel satisfied. Job satisfaction has successfully mediated the relationship between work-life balance variables and employee performance. This research is expected to improve employee performance through work-life balance and job satisfaction. Work-life balance is essential in determining employee performance related to work in any company. With the busyness of the workplace, it isn't straightforward for employees to maintain a fair work-life balance. Such a situation will have an impact on workers physiologically and psychologically. Companies must strive to improve the welfare of workers in the work-life balance of employees, such as implementing flexible schedules, equipping the workplace with facilities to relax, and holding activities related to employee hobbies so that employees feel comfortable and satisfied at work and can raise morale.